ANALISIS KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Pedagang Ikan di Pasar Kerato) - Wahyu Haryadi; Nining Sudiyarti; Egi Kurniawan; I Ismawati; Rosyidah Rachman (Pusat Riset dan Publikasi, 2020)
This study aims to determine the effect of product quality (X1) and service quality (X2) on customer satisfaction of fishmongers in Kerato Market (Y), either partially or simultaneously. This research is associative research, which aims to analyze the influence or relationship between two or among more variables. The data in this research is quantitative in the form of respondents' responses that are collected by distributing a questionnaire. The respondents in this study were 30 customers in Kerato market who selected by accidental sampling. Data analysis performed multiple linear regression analysis techniques, partial hypothesis testing (t- test), simultaneous hypothesis testing (F-test) and determination coefficient test (R2). The findings of this study indicate that both product and service quality affect on customer satisfaction of fishmongers in Kerato market, either partially or simultaneously. The t-count of each variable of product quality and service quality are 2,226 and 2,491, which is greater than the t- table at ? = 5%, which is 2,051. While the F-count value of the test result is 17,438, which is greater than the F-table value at ? = 5%, which is 3,35. The ability of the variable product quality and service quality in explaining the variation of changes in the customer satisfaction variable of fishmongers in Kerato market is 42,6% while the rest 57,4% can be explained by other variables outside the scope of this study.